Factors Affecting Performance on a Screening Tool in Persons with Amyotrophic Lateral Sclerosis - Stierwalt, Jordan; Stierwalt, Julie A.G.; Clark, Heather; Burda, Angela; Benavidez Kiley, Hanna; Collins, Erica; Kortemeyer, Morgan; Miller, Elizabeth; Peckenschneider, Grace; Schieltz, Elizabeth; Shah, Yashvi; Simon, Kayleigh (Seminars in Speech and Language, 2024)
Persons with amyotrophic lateral sclerosis (PALS) are at risk of developing cognitive impairments and frontotemporal dementia (FTD). This study examined the relationship between performance of the ALS-Cognitive Behavioral Screen (ALS-CBS) and the demographic parameters of sex, education, time post–ALS diagnosis, and severity of symptoms. Data were collected retrospectively from 69 participants seen at the Mayo Clinic. Correlations were conducted on the ALS-CBS total scores and subsection scores and the above listed parameters; t-tests were conducted between participant subgroups. No statistically significant relationships or differences occurred between the ALS-CBS or its subsections and the variables measured with exception of age and the attention subsection. Older participants had lower ALS-CBS attention subsection scores. Based on the ALS-CBS scores, most participants had some degree of cognitive impairments: 43 had suspected cognitive impairment, 8 had suspected FTD; 18 fell within the normal range of cognitive function. Overall, the variables of sex, education, time post-diagnosis, and severity of symptoms do not appear to influence ALS-CBS scores. It is recommended cognitive screenings be completed for all PALS due to the high risk for developing cognitive impairments and FTD. Such knowledge can help clinicians develop assessment and treatment plans.
Keywords: ALS; cognition; neurodegenerative; adults